Restorative justice inside prison: enacting the promise of emancipatory pedagogy. Issue 2 (3rd April 2022) - Beck, Elizabeth; Erich, Shane; Foster, Andrew; Nour, Sacad; Higinbotham, Sarah
ABSTRACT: Incarcerated people who study critical theory and emancipatory pedagogy inside prison classrooms can be frustrated by an inability to practice its goals of removing the barriers between faculty and students and creating a more just and democratic society. Inside prison, the theory of emancipatory learning is immensely empowering, but its practice is fraught by the intersecting, oppressive technologies of the prison world. In this article, three incarcerated students and two faculty who teach in prison trace how integrating restorative justice practices bridged emancipatory theory into actual practice. We demonstrate that incarcerated scholars who are equipped with restorative justice training can mitigate prison's disempowering structures.